2014
DOI: 10.1093/gbe/evu192
|View full text |Cite
|
Sign up to set email alerts
|

Natural Selection on Coding and Noncoding DNA Sequences Is Associated with Virulence Genes in a Plant Pathogenic Fungus

Abstract: Natural selection leaves imprints on DNA, offering the opportunity to identify functionally important regions of the genome. Identifying the genomic regions affected by natural selection within pathogens can aid in the pursuit of effective strategies to control diseases. In this study, we analyzed genome-wide patterns of selection acting on different classes of sequences in a worldwide sample of eight strains of the model plant-pathogenic fungus Colletotrichum graminicola. We found evidence of selective sweeps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 82 publications
3
41
0
Order By: Relevance
“…There was transcript evidence for only one of them (Additional file 5: Table S4). The apparent low number of strain-specific SSPs in C. graminicola is consistent with an earlier report [120] that suggested that differences in expression may be more important than presence-absence polymorphisms for pathotype identity.…”
Section: Resultssupporting
confidence: 90%
“…There was transcript evidence for only one of them (Additional file 5: Table S4). The apparent low number of strain-specific SSPs in C. graminicola is consistent with an earlier report [120] that suggested that differences in expression may be more important than presence-absence polymorphisms for pathotype identity.…”
Section: Resultssupporting
confidence: 90%
“…Interestingly, our previous genome‐wide survey of selection in C. graminicola did not detect positive selection in the coding sequence of these genes. Instead, we found evidence of positive selection in the flanking non‐coding parts of the gene, suggesting selection for the transcriptional profile (Rech et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Both loci differentiated samples from the Aleutian Islands from other samples. It is unclear if the EST s linked to the loci used in this study are under selection, but many studies have identified natural selection operating on markers linked to coding regions in other organisms (Bustamante et al ., ; Elmer et al ., ; Rech et al ., ). The results from this analysis suggest that selection may contribute to differentiation of Aleutian Island samples and further investigation is warranted.…”
Section: Discussionmentioning
confidence: 97%